2013
DOI: 10.1021/cg400179p
|View full text |Cite
|
Sign up to set email alerts
|

Toward Phase Quantification at the Nanoscale Using the Total Scattering Pair Distribution Function (TSPDF) Method: Recrystallization of Cryomilled Sulfamerazine

Abstract: One of the most challenging problems facing the pharmaceutical industry is to identify and quantify the phase fractions in mixed phase samples that contain crystalline, nanocrystalline, and amorphous components. Here we demonstrate an approach that accomplishes this using high energy X-rays coupled with total scattering pair distribution function (TSPDF) analysis by studying samples of sulfamerazine, a sulfonamide antibiotic drug, recrystallizing from a cryomilled-induced amorphous state. Samples milled under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 22 publications
0
58
0
Order By: Relevance
“…The main emphasis has been on the thermodynamics of the polymorph transformations and on mechanical properties such as millability, etc. (7,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Zhang et al reported that the thermodynamic transformation of Form II to Form I happens between 50-54 o C, (22) while in our previous work, we discovered that Form I goes to Form II on ball milling for an hour at room temperature. (8) Milling at low temperatures leads to the amorphization of both forms.…”
Section: Introductionmentioning
confidence: 85%
“…The main emphasis has been on the thermodynamics of the polymorph transformations and on mechanical properties such as millability, etc. (7,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Zhang et al reported that the thermodynamic transformation of Form II to Form I happens between 50-54 o C, (22) while in our previous work, we discovered that Form I goes to Form II on ball milling for an hour at room temperature. (8) Milling at low temperatures leads to the amorphization of both forms.…”
Section: Introductionmentioning
confidence: 85%
“…In order to obtain PDF patterns of very high quality, the recorded Q-range has to be large. For this reason, the use of short wavelength X-rays and high 2θ diffracting angles is very important [24]. Total scattering data analyzed by PDF methodology may distinguish phases that are amorphous, nanocrystalline, or crystalline, and this methodology provides quantitative information concerning phase contents and local bonding environments [21].…”
Section: X-ray Pair Distribution Function Analysismentioning
confidence: 99%
“…A semi-quantitative measure of the similarities between the ANP structures can be obtained from the PDF data [25] using the Pearson product-moment correlation, R, calculated pair-wise for all PDF datasets,…”
Section: Structural Environmentmentioning
confidence: 99%
“…Thus R allows us to gauge how similar/dissimilar the structures are without knowing specific details of atomic coordinates and bond angles etc. [25].…”
Section: Structural Environmentmentioning
confidence: 99%